The Factors that Determine Interest to Use of Mobile Payment: Study on the Students of Garut University, Indonesia - Ramdhani, Abdullah; Alamanda, Dini Turipanam; Harisana, Muhammad Husna; Akbar, Gugun Geusan (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2020)
Abstract. Mobile payment is generally a payment tool in the form of software available in smartphones to make it easier for its users to make transactions anytime and anywhere his research aims to give empirical evidence of the influence of perceived ease of use, perceived usefulness, trust, and security on the interest in the use of mobile payment in Garut University students. We collect questionnaires from 100 students that are selected using the proportionate sampling method. The data is then analyzed using multiple linear regression. The analysis’ results show that both perceived of benefit and security variables partially has a positive effect while the perceived ease of use and trust has an insignificant effect on the interest in using mobile payments. This study provides an essential insight into how academic users in rural areas in Indonesia adopt electronic payment technologies.Keywords: Perceived ease of use, Perceived of usefulness, Trust, Security, Interests.